Age-related neutrophil activation in Hermansky-Pudlak Syndrome Type-1 - Lourdes Marinna Caro-Rivera; Sonya Malavez-Cajigas; Mercedes Lacourt-Ventura; Andrea P. Rivera-Torres; Dorca E. Marcano-Jiménez; Pablo López-Colon; José Muñiz-Hernández; Enid Rivera-Jiménez; Mónica Egozcue-Dionisi; Rosa Román-Carlo; Wilfredo De Jesús-Rojas; Marcos J. Ramos-Benítez (Orphanet Journal of Rare Diseases)
Abstract Hermansky-Pudlak Syndrome (HPS) type 1 (HPS-1) is an autosomal recessive disorder characterized by oculocutaneous albinism, platelet dysfunction, and pulmonary fibrosis (HPS-PF), the leading cause of mortality in these patients. HPS-PF manifests earlier than idiopathic pulmonary fibrosis, typically between 30 and 40 years of age. The etiology and drivers of HPS-PF progression remain poorly understood, and no FDA-approved therapies exist. Neutrophil extracellular traps (NETs) and neutrophil-derived mediators have emerged as key players in fibrosis, promoting lung injury, inflammation, and fibroblast activation. This study evaluates the role of neutrophil activation in age-related changes in patients with HPS-1, focusing on differences in inflammatory markers, neutrophil granules, and NETosis capacity. We observed significantly elevated levels of NETs, neutrophil granule proteins (NE, NGAL, LF), and inflammatory cytokines (IL-8, IL-6) in patients with HPS-1 older than 40 years compared to younger patients and healthy controls. Additionally, fibrosis-related markers (MMP-7 and MMP-8) were significantly higher in older patients. Elevated levels of anandamide (AEA), a circulating marker of HPS-PF, were positively associated with neutrophil granule markers in older patients, suggesting its association with fibrosis. Neutrophils from older patients also demonstrated increased NETosis capacity. These findings suggest that age-related neutrophil activation may contribute to an inflammatory environment that promotes fibrosis progression in HPS-1.